Cow’s Milk Containing Avian Influenza A(H5N1) Virus — Heat Inactivation and Infectivity in Mice - Guan, Lizheng; Eisfeld, Amie J.; Pattinson, David; Gu, Chunyang; Biswas, Asim; Maemura, Tadashi; Trifkovic, Sanja; Babujee, Lavanya; Presler, Robert; Dahn, Randall; Halfmann, Peter J.; Barnhardt, Tera; et al. (The New England journal of medicine, 2024)
Influenza A(H5N1) virus has been found in cow’s milk, and H5N1 genetic material has been identified in the commercial milk supply. In this report, investigators assess the effect of heat inactivation on viability of the virus.